Das Verhältnis von Industrie und Finanzsektor unter der Finanzialisierung1 - Müller, Julian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
How does financialisation affect the relationship between non-financial industrial capital and finance? This article argues that their relationship must not be conceived of as an external one, i.e. as the more or less close connection between institutionally separate economic sectors. Financial dominance should be seen instead as something that is internal to industrial capital. The theory and practice of shareholder value are the most prominent expression of this. Marx’ analysis of the different circuits of industrial capital (in Vol. II of Capital) helps to understand the historically variable modes of articulation between non-financial industry and finance. Furthermore it provides conceptual tools to grasp the current financial dominance within industrial capital and can thus help to understand how it differs from the finance capital described by Hilferding.